2016
DOI: 10.1016/j.vaccine.2016.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Development of a stable liquid formulation of live attenuated influenza vaccine

Abstract: HighlightsMultiple excipients were screened for their ability to stabilize influenza vaccine.Identified a liquid formulation with storage stability for one year at 2–8 °C.A stable liquid formulation may lead to wider use of influenza vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Only a small number of formulations for liquid phage product have been published, which is probably due to the stability issues of these methods (Ahiwale et al, 2013;. Inspiration to design liquid formulations for phage might be found in liquid formulations for live virus vaccines for aquaculture, such as White's et al contribution to the subject (White et al, 2016).…”
Section: Stabilizing and Delivering Phages Thanks To Galenicsmentioning
confidence: 99%
“…Only a small number of formulations for liquid phage product have been published, which is probably due to the stability issues of these methods (Ahiwale et al, 2013;. Inspiration to design liquid formulations for phage might be found in liquid formulations for live virus vaccines for aquaculture, such as White's et al contribution to the subject (White et al, 2016).…”
Section: Stabilizing and Delivering Phages Thanks To Galenicsmentioning
confidence: 99%
“…However, it was found that between 0.3 and 1.0 M osmolytes have the ability to cause virus flocculation . Yet, the flocculation system does not change the infectivity of the virus, which was the measure of stability for the influenza virus study, therefore the study of influenza virus stability and this work are not necessarily contradictory to one another.…”
Section: Discussionmentioning
confidence: 92%
“…It has also been determined that osmolytes can stabilize proteins and are often used in protein formulations . Influenza virus formulations can also be stabilized with concentrations of osmolytes around 0.5 M . However, it was found that between 0.3 and 1.0 M osmolytes have the ability to cause virus flocculation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the need of a cold-chain during distribution and storage is expensive and difficult to guarantee especially in developing countries (Soema et al, 2015). Therefore, development of tools aiming at improving antigen stability and driving freeze-drying manufacturing processes by including excipients to the formulation would greatly improve the shelf life, transport and storage duration of influenza vaccines (Geeraedts et al, 2010;Soema et al, 2014;White et al, 2016).…”
Section: Discussionmentioning
confidence: 99%